The merits of entomophagy in the post COVID-19 world. (April 2021) - Doi, Hideyuki; Gałęcki, Remigiusz; Mulia, Randy Nathaniel
Abstract: Background: In 2020, human society underwent several drastic changes due to the coronavirus disease 2019 (COVID-19) pandemic, which generated an unprecedented global impact. Since the onset of the COVID-19 pandemic, various pressing concerns underlying food security, such as transport, production, and maintenance of the supply chain, have been raised. Scope and approach: The present study aimed to describe and review the merits of entomophagy in the post COVID-19 world, especially with regard to the low risk for zoonotic disease spread, high production rate, and future prospects for inducing entomophagy to enhance the diversity in the food system in comparison to conventional livestock. Key findings and conclusions: The advantages of entomophagy in the post COVID-19 world have been elucidated herein, with particular emphasis on the minimal risk of zoonotic disease transmission and production efficiency, in addition to the future goal of establishment of entomophagy to expand redundancy and diversity in the food system as against the utility of conventional livestock. In the current scenario, as well as in the post COVID-19 situation, boosting entomophagy may play a pivotal role in global food security, as the aspects already touched upon have amply demonstrated. Highlights: Under COVID-19 pandemic, various pressing concerns underlying food security. We describe and review the merits of entomophagy in the post COVID-19 world. Merits are low risk of zoonotic disease transmission and production efficiency. Boosting entomophagy may play a pivotal role in global food security.